Eco-friendly bio-based adhesive for plywood from natural rubber latex (NRL)-blended isocyanate cross-linked starch - Soubam, Triveni; Gupta, Arun; Saidatul Shima, Jamari (Springer, 2022)
Synthetic adhesives used in the production of plywood are a matter of concern because of the emission of carcinogenic gas formaldehyde, increased environmental pollution, and the depletion of fossil fuels. In this study, a bioadhesive composed of natural rubber latex (NRL) and rice starch was developed. However, rice starch has low moisture resistance, resulting in low adhesion. Thus, to enhance the effectiveness of NRL-blended rice starch-based bioadhesive, rice starch was cross-linked with polymeric 4,4″-diphenylmethane diisocyanate (pMDI) resin, which is an environment-friendly, formaldehyde free, and moisture resistant that is highly compatible with starch. The chemical interaction, viscosity, solid content, and gel time of the developed NRL-isocyanate cross-linked rice starch-based bioadhesive was investigated. The efficacy of the formulated bioadhesive was demonstrated by the fabrication of plywood. The presence of isocyanate and urethane capabilities in the bioadhesive formulations was confirmed by Fourier transform infrared spectroscopy (FTIR). The bioadhesive type Iso-A was discovered to have the highest viscosity of 8270 mPa.s, whereas Iso-B has the shortest gel time of 3.46 min and the highest solid content of 44%; the higher solid content accelerates the gel time. In terms of physical and mechanical properties of plywood, Iso-B has the lowest thickness swelling (TS) value of 13%, lowest water absorption (WA) value of 52% and shear strength value of 1.92 MPa, which corresponds to the ISO 12466–2-2007 standard requirements. Based on the results, NRL-blended isocyanate starch-based bioadhesive could be a good potential raw material for eco-friendly plywood industries with adequate accuracy.